Navigating trade-offs in design for sustainability and circularity: A tool for decision making leveraging narratives and multiple criteria decision analysis - Giácomo Parolin; Jacob Arnbjerg; Tim C. McAloone; Daniela C.A. Pigosso (Journal of Cleaner Production, 2025)

Enabling environmental sustainability and circularity assessment in technology development: The Value-Impact Scanner - Giácomo Parolin; Jacob Arnbjerg; Henriette A. Eriksen; Tim C. McAloone; Daniela C.A. Pigosso (Sustainable Production and Consumption, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Enhanced middle Holocene organic carbon burial in tropical floodplain lakes of the Pantanal (South America) - Giliane G. Rasbold; Michael M. McGlue; José C. Stevaux; Mauro Parolin; Aguinaldo Silva; Ivan Bergier (Journal of Paleolimnology, 2021)

Onopordum illyricum L., a Mediterranean plant, as a source of anti HIV-1 compounds - C. Sanna; D. Rigano; P. Cortis; A. Corona; M. Ballero; C. Parolin; C. Del Vecchio; G. Chianese; E. Saccon; C. Formisano; E. Tramontano; F. Esposito (Plant Biosystems, 2018)

Survey of laboratory-acquired infections around the world in biosafety level 3 and 4 laboratories - N. Wurtz; A. Papa; M. Hukic; A. Di Caro; I. Leparc-Goffart; E. Leroy; M. P. Landini; Z. Sekeyova; J. S. Dumler; D. Bădescu; N. Busquets; A. Calistri; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Vaginal microbiome and metabolome highlight specific signatures of bacterial vaginosis - B. Vitali; F. Cruciani; G. Picone; C. Parolin; G. Donders; L. Laghi (European Journal of Clinical Microbiology & Infectious Diseases, 2015)